2019
DOI: 10.1073/pnas.1913714116
|View full text |Cite
|
Sign up to set email alerts
|

Sustained wood burial in the Bengal Fan over the last 19 My

Abstract: The Ganges–Brahmaputra (G-B) River system transports over a billion tons of sediment every year from the Himalayan Mountains to the Bay of Bengal and has built the world’s largest active sedimentary deposit, the Bengal Fan. High sedimentation rates drive exceptional organic matter preservation that represents a long-term sink for atmospheric CO2. While much attention has been paid to organic-rich fine sediments, coarse sediments have generally been overlooked as a locus of organic carbon (OC) burial. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 57 publications
2
53
0
Order By: Relevance
“…Current estimates of carbon fluxes in the ocean (Burdige, 2007;Blair and Aller, 2012) posit that sandy fractions are POC free. Yet a recent study (Lee et al, 2019) has found that abundant wood has been buried in sands in the Bengal Fan (Bay of Bengal, Indian Ocean) for the last 19 m.y. Other studies have described organic-rich layers in sandy deep-sea turbidites (Saller et al, 2006;Zavala et al, 2012;Sparkes et al, 2015;Leithold et al, 2016), in some cases even within sands of units Ta and Tb, depending on the density and size of organic debris (McArthur et al, 2016;Schnyder et al, 2017).…”
Section: Sand Mudmentioning
confidence: 99%
See 1 more Smart Citation
“…Current estimates of carbon fluxes in the ocean (Burdige, 2007;Blair and Aller, 2012) posit that sandy fractions are POC free. Yet a recent study (Lee et al, 2019) has found that abundant wood has been buried in sands in the Bengal Fan (Bay of Bengal, Indian Ocean) for the last 19 m.y. Other studies have described organic-rich layers in sandy deep-sea turbidites (Saller et al, 2006;Zavala et al, 2012;Sparkes et al, 2015;Leithold et al, 2016), in some cases even within sands of units Ta and Tb, depending on the density and size of organic debris (McArthur et al, 2016;Schnyder et al, 2017).…”
Section: Sand Mudmentioning
confidence: 99%
“…In contrast, the role of marine sands in global POC burial has long been overlooked (Burdige, 2007). Yet woody debris associated with sands in submarine fans is increasingly being recognized as a major terrestrial POC pool (Leithold et al, 2016;Lee et al, 2019). Submarine fans are formed by turbidity currents, which domi-nate sediment deposition across vast areas of the seabed (Bouma et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Sediment volumes preserved in the BNFS record the denudation history of the Himalaya Range and have been used to estimate denudation rates over geological timescales (France-Lanord et al, 1993;Einsele et al, 1996;M etivier et al, 1999), whereas variations in the nature and rate of sediment accumulation were related to regional climatic variations (France-Lanord & Derry, 1994;Weber et al, 2003;). Recently, studies have shown the importance of the Bengal Fan in the carbon cycle via uplift and denudation processes in the India-Asia collision zone (carbon dioxide consumption from silicate weathering) and marine sedimentation (burial of organic carbon), which makes the Bengal Fan a net sink of CO 2 at a global scale (France-Lanord & Derry, 1997;Galy et al, 2007;Lee et al, 2019).…”
Section: Bengal Depositional Fanmentioning
confidence: 99%
“…However, perhaps the largest source of uncertainty relates to the dynamics of particulate OC transport versus clastic sediment in relation to its mobility following landslide events. While the general link between the two phases has been demonstrated (Galy et al, 2015;Hilton et al, 2012), there is also evidence that discrete clasts of woody debris can be sorted by flowing water (Hilton et al, 2015;Lee et al, 2019), and its transport behaviour different from the clastic load due to a lower density and different particle shape (Turowski et al, 2016).…”
Section: Limitations Of the Approachmentioning
confidence: 99%